Live broadcast impact in teaching and learning process during Covid-19 pandemic - Andi Sahtiani Jahrir; Muhammad Tahir (Center for Humanities and Innovation Studies, 2020)
This study aims to find out the types of live broadcast media used in the teaching and learning process and explore the constraints experienced by students regarding the learning process during the Covid-19 pandemic. This study applied a qualitative study type. The participants in this study were students of the Indonesian Language and Literature department in the Faculty of Languages and Literature, Universitas Negeri Makassar, Indonesia, in 2019-2020. This study found that the learning media used in the teaching and learning process for a regular meeting during the Covid-19 pandemic as live broadcast application were Zoom, Google Meet, and Streamyard. However, students also experienced that some lecturers only used live broadcast for online examination regarding evaluating the students’ assignment progress submitted to Google Classroom. Students also reported that lecturers use live broadcast applications to teach and other applications, such as Google Classroom and LMS. This study also found out the constraints experienced by students regarding the learning process during the Covid-19 pandemic. This study revealed that the students experienced some constraints in the learning process during the Covid-19 pandemic, such as a large amount of data or quotas in use, the inadequate time provided by media of live broadcast, which is up to about forty minutes. Also, unsupportive signals always make weak audio sounds and sometimes close the application, making it difficult for students to comprehend the materials. Therefore, this study recommends that the lecturers maximize the teaching and learning process to anticipate time, place, and internet data packages as students’ constraints by recording the live broadcast in the form of YouTube live streaming.